Re-gendering discourse in Adrienne Rich's Snapshots of a Daughter-in-Law - Hassan, Mohamad Fleih; Talif, Rosli (Malaysian Association of Modern Languages, 2014)
Adrienne Rich is one of the most famous American feminist poets in the modern world. She stated that women are gendered in the patriarchal society to be inferiors, victims and weak. In Rich’s poem, Snapshots of a Daughter-in-Law, she proposes that re-gendering discourse will help women to prove their own female identities away from the patriarchal heterosexual discourse which oppressed women along history. This article focuses on Adrienne Rich’s poem in the light of her feminist discourse of re-gendering, through tracing the semiotic elements within the symbolic patriarchal language. This is done by applying Kristeva’s concept of the Semiotic and the Symbolic to be the framework of the study. Kristeva states that the semiotic is maternal and the symbolic is masculine, and both of these modalities are needed in the signifying process. Therefore, Rich regains to language the feminine principle which is the only way to create an unprejudiced language that is fair to the masculine and feminine needs.